Customer satisfaction among Utusan Melayu’s customer toward product, price and content of the newspaper / Dhabitah Ruslan - Ruslan, Dhabitah (Faculty of Business and Management, 2009)
The purpose of this study was to investigate the relationship of the selected independent variables : product , price and newspaper’s content with dependent variable which is customer satisfaction. In order to provide a guide in the study, three hypotheses were formulated.